Taṣawwur Muqtaraḥ li-Ta‘zīz ba‘ḍ al-Qiyam al-Akhlāqīyah bi-Manāhij Ta‘līm al-Lughah al-‘Arabīyah li-al-Nāṭiqīna bi-Ghayrihā fī al-Mamlakah al-‘Arabīyah al-Su‘ūdīyah - 'Adil bin 'Ayid al-Mogazawi (Al-Ma‘rifah, 2018)
The current study aimed at identifying the indicators of thought immunity among the Saudi University students in the light of some contemporary challenges, namely, extremism, fanaticism and atheism. The researcher made use of the descriptive method for fulfilling the purpose of the study. Furthermore, a questionnaire was developed for collecting the target data. The questionnaire was administered to 90 staff members and 3000 university students (males and females) in the Saudi universities. The study depicted the most significant indicators of the thought immunity and the most and the least available thought immunity indicators among the study participants. The results of the study also revealed that there were statistically significant differences among the participants responses due to the specialization variable. There were statistically significant differences among the study participants in the light of the study year, gender and specialization variables.